A new method for the preparation of high-purity CO2-absorbing Li3NaSiO4 powder using lithium silicate and sodium carbonate. Issue 39 (20th September 2022) - Iwasaki, Shumpei; Shido, Kosuke; Hashimoto, Takuya
Abstract : By changing starting material from the mixture of Li2 CO3 /Na2 CO3 /SiO2 to Li4 SiO4 /Li2 SiO3 /Na2 CO3, powder Li3 NaSiO4 with higher purity and more homogeneous particle size, showing higher amount of CO2 absorption, was obtained. Abstract : The starting materials and temperature for the preparation of Li3 NaSiO4 powder, which has attracted attention as a CO2 absorbent, were optimized in this study. Mixtures of Li2 CO3, Na2 CO3, and SiO2 as well as Li4 SiO4, Li2 SiO3, and Na2 CO3 were subjected to thermogravimetry-differential thermal analysis (TG-DTA) to elucidate their reaction mechanisms. The phase, morphology, specific surface area, and CO2 absorption characteristics of the powder specimens that were obtained by heating the two mixtures were examined by X-ray diffraction (XRD), secondary electron microscopy (SEM), N2 adsorption isotherm and isothermal TG-DTA. Melted LiNaCO3 was generated via the heat treatment of the Li2 CO3, Na2 CO3, and SiO2 powder mixture, yielding a low-purity bulk specimen with inhomogeneous particle size. However, the use of the Li4 SiO4, Li2 SiO3, and Na2 CO3 mixture as a starting material ensured that no liquid phase was generated during heat treatment and successfully yielded Li3 NaSiO4 powder which was purer than the product derived from the Li2 CO3 /Na2 CO3 /SiO2 mixture, presumably because of the lower volatility of Li and Na in the solid phase than that in the liquid phase of LiNaCO3 . The Li3 NaSiO4 powder derived from Li4 SiO4, Li2 SiO3, and Na2 CO3 showed a slightly larger surface area with homogeneous particle size and almost identical CO2 absorption kinetics compared to those of the product obtained from Li2 CO3, Na2 CO3, and SiO2, in addition to absorbing a higher amount of CO2 owing to its higher purity.